2014
DOI: 10.1152/advan.00162.2012
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory study of factors related to educational scores of first preclinical year medical students

Abstract: The relationships among the scores of major subjects taught in the first preclinical year of a Thai medical school, previous academic achievements, and daily life activities are rarely explored. We therefore performed an exploratory study identifying various factors possibly related to the educational scores of these medical students. Questionnaires were sent out to all first preclinical year medical students, with 79.8% being returned (245/307 questionnaires). Positive correlations were revealed between the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
20
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 16 publications
9
20
0
2
Order By: Relevance
“…While this is a novel finding for health science students, previous studies have identified a similar relationship in medical cohorts (Sitticharoon, Srisuma, Kanavitoon, & Summachiwakij, 2014). Anatomy and physiology are integral components of a health science degree, indeed many anatomists believe that mastering the somewhat rote learning style of anatomy can aid students across multiple fields of study (Pandey & Zimitat, 2007).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…While this is a novel finding for health science students, previous studies have identified a similar relationship in medical cohorts (Sitticharoon, Srisuma, Kanavitoon, & Summachiwakij, 2014). Anatomy and physiology are integral components of a health science degree, indeed many anatomists believe that mastering the somewhat rote learning style of anatomy can aid students across multiple fields of study (Pandey & Zimitat, 2007).…”
Section: Discussionmentioning
confidence: 56%
“…Human biology appears to be a common intuitive predictor for a health science degree although the teaching delivery of BMS100 may be disparate and the theory more involved. Nevertheless, student background in human biology is purportedly of help with study techniques, familiarity with terminology, and understanding anatomical concepts (Sitticharoon et al, 2014). It is well recognised in the teaching literature that previous exposure to concepts, even an awareness of the degree of depth within topics, enhances student aptitude for difficult content.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pre-clinical medical education is already challenged to expose students to a large amount of information in a very short time, and students spend large amounts of their time outside of class studying to stay caught up with material [17]. Thus, putting additional requirements for students to acquire information on their own outside of class could further impair student mental health and well-being [10].…”
Section: Introductionmentioning
confidence: 99%
“…In that paper, only 4.7-9.7% of students were provided handouts read textbooks after lectures and before examinations. The advantages of reading are supported by a recent study showing that the percentage of expected reading is a factor involved in producing good academic results in the first pre-clinical year (Sitticharoon et al 2014). Proper assessment drives proper learning styles.…”
Section: Do Medical Students Really Need Lecture Handouts?mentioning
confidence: 94%